Digital tools to promote remote lesson study. Issue 2 (2nd February 2021) - Weaver, Joanna C.; Matney, Gabriel; Goedde, Allison M.; Nadler, Jeremy R.; Patterson, Nancy
Abstract : Purpose: The authors propose that a digital instructional delivery format of lesson study (LS) may have the potential to amplify particular aspects of traditional, face-to-face LS. Design/methodology/approach: This is a qualitative case study, using data triangulation, member checking and an inductive approach to open-coding utilizing grounded theory to identify codes and themes. Findings: Digital tools promoted LS and learning, allowing for rigorous collaboration, synchronous observations, data collection and feedback, leading to deeper understanding. Research limitations/implications: Digital tools used in the online LS process changed how instructional planning can be researched, analyzed and written collaboratively and impacted the fluidity of a lesson, the ease of observation and reflection, student engagement and the researchers' and students' ability to share ideas in real time. Practical implications: LS can be integrated into online teacher education programs to engage students in online learning and promotes engagement, peer interaction and student voice. The use of these digital tools is not restricted just to remote instructional contexts. Social implications: LS reduces teacher isolation, builds a collaborative community of teachers and increases instructional motivation. Educators across schools, universities or districts can integrate online LS into remote teacher education programs and online courses. Originality/value: This study is original work that has not been published elsewhere.